Morphological and molecular separation between Macrocamptoptera grangeri Soyka and M. metotarsa (Girault) (Hymenoptera: Mymaridae). Issue 9 (18th March 2020) - Triapitsyn, Serguei V.; Dominguez, Chrysalyn; Huber, John T.; Japoshvili, George; Heraty, John M.
ABSTRACT: Based on morphological and molecular evidence, the European fairyfly Herulia sundholmi Hedqvist syn. n. (Hymenoptera: Mymaridae) is removed from previous synonymy with the Nearctic Macrocamptoptera metotarsa (Girault), and synonymised with the Palaearctic M. grangeri Soyka, which is newly recorded from Georgia, Slovakia and Spain. Macrocamptoptera bulagarica (Donev) syn. n., known from Bulgaria and Italy, is also synonymised with M. grangeri . An updated key to females of the three currently recognised species of the rarely collected genus Macrocamptoptera Girault is given.